Teaching Controversial Issues in the Classroom: A Study of Educators' Strategies for Promoting Critical Thinking and Preventing Extremism - Muhammad Ajmal Khuhro; Dr. Rizwana Muneer (Social Science Review Archives, 2025)
This qualitative study examines how educators in Karachi navigate the challenges of teaching controversial issues to cultivate critical thinking and reduce susceptibility to extremist narratives. Data were collected via semi-structured interviews with 20 educators from public and private secondary schools and universities, along with two focus groups (n = 10) representing diverse disciplines and teaching levels. Participants were purposively sampled to ensure representation across sector, subject area, and teaching experience. Using reflexive thematic analysis, four key themes emerged: (1) Structured Openness—scaffolded dialogue strategies to enable safe engagement with sensitive issues; (2) Curricular Rigidities—assessment and textbook-driven constraints limiting dialogic pedagogy; (3) Contextual Risk Management—balancing open discussion with safety and community pressures; and (4) Capacity Gaps—limited professional development and resources for critical-thinking instruction. Educators viewed critical thinking as a protective factor against oversimplified extremist frames but faced systemic and sociopolitical barriers to sustained practice. The study contributes an empirically grounded model linking dialogic strategies to perceived extremism-prevention outcomes in constrained contexts, and offers policy recommendations targeting teacher professional development, curriculum reform, and school–community collaboration.